Fun and games at Malory towers - Cox, Pamela; Blyton, Enid. (b, 2013)
New girl Millicent clashes with the feisty June over the school's priorities: a music concert or tennis tournament? But both pale into insignificance when it's found there's a thief in the fifth form.
Keywords: Malory Towers (Imaginary place) -- Juvenile fiction; Boarding schools -- Juvenile fiction; Boarding schools -- Fiction; Boarding schools